Acute effect of functional exercise through the use of battle rope on skeletal muscles of tennis court student-athletes - Mahmuddin; Prima, Asep; Siahaan, David; Ardilla, Rafika (Journal Sport Area, 2024)
Background Problems: There has not been much research on how exercise strategies affect muscle soreness and activation patterns. Research Objectives: This study examines the acute effects of rope-based functional training on muscle group pain response in student athletes at the Faculty of Sport Science, Universitas Negeri Medan tennis court. Methods: An experimental method and a pre-post-test time series design were used for analysis. Seven samples were selected using purposive sampling. All participants engaged in a warm-up, a central phase of rope training with a maximum of three sets per exercise, ten hand swing repetitions, a one-minute break between sets, and a cooling phase. Three 100-mm VAS and painometer data collection sessions were conducted. At a 0.05 significance level, the research data was examined using one-way ANOVA for normal data and Friedman for aberrant data. Both studies used SPSS 16.0. Findings and Results: The trial demonstrated that rope training induces soreness in all working muscles. However, no muscle group exhibited discomfort above 50 mm. Conclusion: In order to optimally activate muscles, determine exercise doses and blood lactate levels in relation to muscle discomfort, it is necessary to understand how battle rope training reduces muscular soreness and improves muscle activation in student-athletes on the tennis court. This understanding can inform the development of personalised training programmes and injury prevention techniques.